2013
DOI: 10.1016/j.resp.2013.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical consequences of altered chemoreflex control

Abstract: Control of ventilation dictates various breathing patterns. The respiratory control system consists of a central pattern generator and several feedback mechanisms that act to maintain ventilation at optimal levels. The concept of loop gain has been employed to describe its stability and variability. Synthesizing all interactions under a general model that could account for every behavior has been challenging. Recent insight into the importance of these feedback systems may unveil therapeutic strategies for com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 126 publications
(172 reference statements)
1
23
0
Order By: Relevance
“…[44][45] Metabolic acidosis enhances peripheral chemosensitivity, causing marked alterations in the ventilatory recruitment threshold of pCO 2 and ultimately predisposing central or OSA. 39,[46][47] It is thought that hypocapnia (reduced pCO 2 levels), a respiratory compensatory mechanism during metabolic acidosis, enhances chemoreceptor sensitivity to CO 2 , thus altering chemoreflex control, and ultimately destabilizing respiratory control during sleep by decreasing pCO 2 levels below the apneic threshold. [37][38][39]41,[48][49][50][51] On the other hand, chemoreflex sensitivity is markedly altered by hypercapnia.…”
Section: Chemoreflex Responsivenessmentioning
confidence: 99%
“…[44][45] Metabolic acidosis enhances peripheral chemosensitivity, causing marked alterations in the ventilatory recruitment threshold of pCO 2 and ultimately predisposing central or OSA. 39,[46][47] It is thought that hypocapnia (reduced pCO 2 levels), a respiratory compensatory mechanism during metabolic acidosis, enhances chemoreceptor sensitivity to CO 2 , thus altering chemoreflex control, and ultimately destabilizing respiratory control during sleep by decreasing pCO 2 levels below the apneic threshold. [37][38][39]41,[48][49][50][51] On the other hand, chemoreflex sensitivity is markedly altered by hypercapnia.…”
Section: Chemoreflex Responsivenessmentioning
confidence: 99%
“…The propensity for ventilation to oscillate (one potential source of variability) can be encapsulated by the engineering concept of loop gain, which describes the overall stability of the feedback system controlling ventilation (28). The ventilatory control system can be characterized by three main components: 1) the "controller gain," which is the response as a change in ventilation per change in unit PaCO 2 or PaO 2 (related to chemical drive); 2) the "plant gain," which can be expressed as the change in PaCO 2 or PaO 2 per unit change in ventilation; and 3) the circulation delay between the lungs and the peripheral and central chemoreceptors (28). Importantly, Khoo in his review illustrates the point that the same amount of ventilatory variability may be found in systems with different levels of stability (20).…”
Section: New and Noteworthymentioning
confidence: 99%
“…The objectives of this study were to describe the variability of resting ventilation [coefficient of variation (CV) of VT and slope], the stability in respiratory control (loop, controller and plant gains characterizing ventilatory-chemoresponsiveness interactions) and the chaotic-like dynamics (embedding dimension, Kappa values characterizing complexity) of resting ventilation in patients with a well-defined dysfunctional breathing pattern characterized by air hunger and constantly decreased PaCO 2 during a cardiopulmonary exercise test. Compared with 14 healthy subjects with similar anthropometrics, 23 patients with hyperventilation were characterized by increased variability of resting tidal ventilation (CV of VT median [interquartile]: 26% [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] vs. 36% [28 -48], P ϭ 0.020; slope: Ϫ6.63 [Ϫ7.65; Ϫ5. 36] vs. Ϫ3.88 [Ϫ5.91; Ϫ2.66], P ϭ 0.004) that was not related to increased chemical drive (loop gain: 0.051 [0.039 -0.221] vs. 0.044 [0.012-0.087], P ϭ 0.149) but that was related to an increased ventilatory complexity (Kappa values, P Ͻ 0.05).…”
mentioning
confidence: 99%
“…Numerous disorders of breathing and cardio-respiratory coupling are associated with dysfunctional chemoreceptor drive mechanisms (Dempsey and Smith 2014;Garcia et al 2013;Perez and Keens 2013;Plataki et al 2013). Brain mechanisms that mediate the separate and joint actions of central chemoreceptors, sensors of brain CO 2 and pH, and the peripheral chemoreceptors are topics of active research and debate (Duffin and Mateika 2013; Nuding et al 2009b;Teppema and Smith 2013;Wilson and Day 2013).…”
mentioning
confidence: 99%